Literatur Review: Laporan Keuangan sebagai Instrumen Deteksi Dini atas Kebangkrutan Perusahaan - Aqilah Miranda; Edya Nashwa Septika; Citra Amelia Parsi; Fitri Yani Panggabean (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research aims to examine in depth the role of financial statements as an instrument for early detection of potential corporate bankruptcy. Through a literature study approach of various scientific sources between 2019 and 2025, this research highlights how information presented in financial statements, such as declining profits, increasing debt, and weakening liquidity, can be an early indicator of deteriorating financial conditions. Various predictive models such as Altman Z-Score, Springate, and Grover are discussed as tools in identifying the level of bankruptcy risk. The results show that the effectiveness of these models is highly dependent on the industry characteristics and financial structure of each company. In addition, the quantitative approach needs to be complemented with qualitative analysis to produce a more accurate diagnosis. The findings reinforce the importance of financial statements as a strategic tool in decision-making as well as an early warning system that can improve a company's preparedness for the threat of bankruptcy.